FOREIGN TRADE OF UKRAINE IN PROCESSED FRUIT AND VEGETABLES - DUKHNYTSKYI, Bogdan; BOTSMAN, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines dynamics of Ukraine's exports and imports in group 20 of the Ukrainian Goods Classification of Foreign Economic Activities "Products of processed vegetables, fruits, nuts" with the allocation of maximum and minimum value indicators over the past ten years. It is established that their largest values were simultaneously achieved in 2024, while the smallest - in 2016. At the same time, overall trade balance for Ukraine often changes from positive to negative and vice versa. Despite the war, export and import indicators have not changed much, continuing to be in the usual range. For today, fruit and vegetable processing has a weak impact on the formation total incomes of agricultural trade’s operators. The geographical and commodity structure of our country's foreign trade in processed fruit and vegetable products analyzed. Most deliveries were made to the countries of the European Union and North America, while the main purchases went from the EU and Asia. Ukraine has a strong concentration in exports of juices, namely apple concentrate, belonging to the main suppliers on the global market, supplementing them with canned tomatoes. Imports are mainly consist of atypical goods for us - nut mixtures, canned olives, pineapples, orange juice. A general assessment of development the world market in the context of international trade in recent years through the prism of its significant growth was made. Countries that occupy leading positions in global exports and imports have been noted. They include individual members of the European Union, the United Kingdom, the United States, China and Japan. Important trends in the domestic market that restrict full development of the processing business in food industry have been characterized. Recommendations for the development of fruit and vegetable processing in the context of domestic food supply and increasing exports are provided.
Keywords: processing; export; import; fruits; vegetables; structure; diversification